Upaya Badan Pengelola Lingkungan Hidup dalam Menanggulangi Tindak Pidana Lingkungan Hidup di Kota Jayapura - Nurul Chaerani Nur (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2019)
This study aims to identify and analyze the efforts of Jayapura’s Environmental Management Agency in tackling environmental crimes and to analyze the hindering factors of environmental crimes. The research method used in this study is the Juridical Empirical research method, approaching the problem by looking at the norms or legal provisions, then connecting it with the facts that exist from the problem. Jayapura’s Environmental Management Agency (BPLH) carries out several activities in an effort to tackle environmental crimes, including conducting socialization of Law Number 32 of 2009, Conducting an inventory and classification of reported environmental crimes, conducting guidance to business actors related to the business or activities, Supervising the business and or activities related to the results of parameter tests. The hindering factors of environmental crime prevention in Papua consist of unavailable funds, wide area, lack of support from decision makers, lack of human resources, lack of supporting facilities and infrastructure.